Causes of Adermatoglyphia: A hurdle to Biometric Authentication - Saelah Batool; Hira Tariq; Muhammad Shahid; Saadiya Siddiqui; Sakina Batool; Shahbaz Aman (Journal of Pakistan Association of Dermatologists, 2022)
Objective: To determine the causes of adermatoglyphia in patients presenting to Services Hospital, Lahore. Methods: This cross-sectional survey was carried out in the Department of Dermatology, Services Hospital, Lahore. All patients were referred by National Database and Registration Authority (NADRA) through Medical Examination Department (MED) of Services Hospital for verification of adermatoglyphia. Detailed history, physical and cutaneous examination was done. Skin of fingers and inkpad prints taken on white paper were evaluated. Causes of adermatoglyphia were assessed and data was recorded. Results: A total of 152 patients of adermatoglyphia were enrolled over a period of two years. Out of them, 96 (63.2%) were males while 56 (36.8%) were females. Mean age of the patients was 41.89 Â± 23.72 years. Among our study population 20 (13.2%) patients had Isolated congenital (idiopathic) adermatoglyphia, 52 (34.2%) patients suffered from Congenital adermatoglyphia associated with a syndrome, while 80 (52.6%) patients presented with acquired causes of adermatoglyphia. Conclusions: It is concluded that adermatoglyphia is a challenge to biometric identification and authentication and is much more common than anticipated. With advancing technologies, other standardized alternative biometric modalities should be made available where fingerprinting is not conclusive. Keywords: Adermatoglyphia; Biometric Authentication, Fingerprinting